Foot‐and‐mouth disease seroprevalence and reporting behaviours in nine northern provinces in Lao PDR: The current situation and challenges for control. Issue 2 (21st February 2021) - MacPhillamy, Isabel; Young, James; Earp, Francesca; Khounsy, Syseng; Windsor, Peter; Toribio, Jenny‐Ann; Bush, Russell
Abstract: Foot‐and‐mouth disease (FMD), caused by the FMD virus (FMDV), is one of the most important of global livestock diseases, impacting even‐toed ungulates and distributed mostly in less developed countries that are home to 75% of the human population. A progressive control pathway for FMD (PCP‐FMD) was developed to assist countries to better manage FMD risks and progress towards control and eradication. This requires evidence of current FMD seroprevalence to enable the informed risk assessment and the disease control planning required to progress along the initial stages of the PCP‐FMD. Despite Laos being an active member of the South East Asia and China FMD campaign, these data have been challenging to obtain. To address this gap, a cross‐sectional seroprevalence study in nine northern Lao provinces was conducted in early 2019. The study sampled 602 large ruminants and 19 goats from 30 villages. Overall, the large ruminant seroprevalence was 43.7% (95% CI 39.7–47.8), and 90% of sampled villages had at least one seropositive animal. Large ruminants suspected of having had clinical FMD in their lifetime were found to have an increased risk of being seropositive (odds ratio 1.96, 95% CI 1.06–3.65, p = .03). An examination of current reporting behaviours of farmers, village veterinary workers and district and provincial officials found that individuals were using their discretion as to whether disease events required reporting along the chain of command. This, plus the lack of a computerized reporting system, contributed to a loss of historical data, potentially compromising progression on the PCP‐FMD. Laos requires ongoing support from donor agencies to improve the current animal disease surveillance system and implement effective FMD control strategies that can enable progress on the PCP‐FMD.